2010
DOI: 10.1016/j.ygyno.2009.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for response to cisplatin-based chemotherapy in advanced cervical carcinoma: A Gynecologic Oncology Group Study

Abstract: Purpose Cisplatin-based combination chemotherapy is considered standard treatment for advanced/recurrent cervical carcinoma; however, the majority of patients do not respond. This study was undertaken to identify the prognostic factors and develop a model predictive of (non-) response to chemotherapy. Methods Four-hundred twenty-eight patients with advanced cervical cancer who received a cisplatin-containing combination in three Gynecologic Oncology Group (GOG) protocols (110, 169 and 179) were evaluated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
95
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(101 citation statements)
references
References 25 publications
(25 reference statements)
3
95
1
2
Order By: Relevance
“…This represents valuable time that may allow patients to receive other promising novel therapies including other types of angiogenesis treatment or immunotherapy to take advantage of what the forefront of translational research has to offer. Additionally in GOG 240, validation of the Moore criteria for identification of patients with poor prognostic factors not likely to respond to cisplatin-based regimens demonstrated that the highest risk patients benefit the most from angiogenesis inhibition with bevacizumab [31,32].…”
Section: Expert Opinionmentioning
confidence: 99%
“…This represents valuable time that may allow patients to receive other promising novel therapies including other types of angiogenesis treatment or immunotherapy to take advantage of what the forefront of translational research has to offer. Additionally in GOG 240, validation of the Moore criteria for identification of patients with poor prognostic factors not likely to respond to cisplatin-based regimens demonstrated that the highest risk patients benefit the most from angiogenesis inhibition with bevacizumab [31,32].…”
Section: Expert Opinionmentioning
confidence: 99%
“…Moore et al (Moore et al, 2010 ) reported five independent prognostic factors for survival outcomes of cisplatin-based chemotherapy in 428 advanced cervical cancer patients from three GOG protocols (GOG 110,169 and 179). These factors included African-American, performance status more than zero, pelvic disease, prior radiotherapy, and time interval from diagnosis to first recurrence less than 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…9 A recent retrospective review of four randomized phase III GOG clinical trials suggested that advanced or recurrent cervical cancer patients who had been previously treated with radiosensitizing-cisplatin showed poorer response to platinum-based chemotherapy than those who had not. 10 With the aim to investigate the effectiveness of non-platinum containing chemotherapy in the same population, GOG has recently initiated a phase III trial (protocol 240) comparing TP versus non-platinum doublet (paclitaxel-topotecan), with or without bevacizumab.…”
Section: Discussionmentioning
confidence: 99%